Chemical stability and bioaccessibility of β-carotene encapsulated in sodium alginate o/w emulsions: Impact of Ca2+ mediated gelation. (June 2016) - Soukoulis, Christos; Cambier, Sébastien; Hoffmann, Lucien; Bohn, Torsten
Abstract: In the present work, 5% (w/w) canola oil-in-water submicron emulsions containing sodium alginate were investigated as β-carotene (0.05% w/w) carriers. O/w emulsions prepared via spontaneous emulsification were Tween-80 (SA, 1 and 1.5% w/w) stabilised. Ionotropic gelation of the o/w emulsions' continuous phase via in situ Ca 2+ release, in the presence (sheared o/g emulsions) or absence (quiescent o/g emulsions) of mechanical stirring (1000 rpm, 6 h) was conducted. β-Carotene chemical stability in both o/w and o/g emulsions following 65 day storage periods at 4, 20 and 37 °C, as well as its bioaccessibility under in vitro oro-gastro-intestinal digestion conditions were evaluated. Oxidative degradation rates of β-carotene ranged from 0.22 to 2.77%/day. Although Ca 2+ -mediated gelation of o/w emulsions' aqueous phase enhanced β-carotene chemical stability, oxidative degradation rates between quiescent o/g (0.07–1.42%/day) and sheared o/g (0.19–1.50%/day) emulsions were comparable. Based on the activation energies of β-carotene degradation calculated by the Arrhenius kinetic model, sheared o/g emulsions exerted the lowest storage temperature dependency, followed by the quiescent o/g and SA containing o/w emulsions. Moderate (ca. 27%) to high (ca. 48%) bioaccessibility of β-carotene was achieved in quiescent and sheared o/g emulsions respectively, showing no dependency on SA content. Contrarily, β-carotene bioaccessibility was reduced from ca. 29–16% for 1 and 1.5% SA containing o/w emulsions. Digesta micellar fractions of o/g emulsions exerted smaller lipid droplet size and lower surface tension values compared to the SA containing o/w emulsions. Therefore, it was postulated that enhanced β-carotene bioaccessibility in o/g emulsions was associated with their higher colloidal stability throughout gastrointestinal passage. Graphical abstract: Highlights: Tween-80 stabilised sub-micron o/w and oil-in-gel (o/g) emulsions with sodium alginate (SA) tested as β-carotene carriers. Sheared and quiescent o/g emulsions were fabricated via Ca 2+ mediated SA gelation. β-Carotene retention throughout storage was enhanced in o/g emulsions. Sheared o/g emulsions exerted highest β-carotene bioaccessibility. SA o/w emulsions were greatly affected by in vitro digestion conditions.